Characterization of the subgingival cultivable microbiota in patients with different stages of periodontitis in spain and Colombia. a cross-sectional study (2021)
The objective was to characterize and compare the subgingival microbiota in patients diagnosed according to the World Workshop on the Classification of Periodontal and Peri-Implant Diseases and Conditions 2018. For this cross-sectional study, Spanish and Colombian subjects (characterized as health/gingivitis, periodontitis in stages I-II or stages III-IV) were clinically assessed, and subgingival samples were taken and processed by culture. The comparisons among patients with periodontal status (and between countries) was made using Mann–Whitney, Kruskal–Wallis, ANOVA and chi-square tests. The final sample consisted of 167 subjects. Eikenella corrodens and Parvimonas micra were more frequently detected in health/gingivitis and Porphyromonas gingivalis in periodontitis (p < 0.05). Higher total counts were observed in Colombia (p = 0.036). In Spain, significantly higher levels of P. gingivalis and Campylobacter rectus were observed, and of Tannerella forsythia, P. micra, Prevotella intermedia, Fusobacterium nucleatum, Actinomyces odontolyticus and Capnocytophaga spp. in Colombia (p < 0.001). P. micra was more prevalent in health/gingivitis and stage I-II periodontitis in Colombia, and P. gingivalis in all periodontitis groups in Spain (p < 0.05). As conclusions, significant differences were detected in the microbiota between health/gingivitis and periodontitis, with minor differences between stages of periodontitis. Differences were also relevant between countries, with Colombia showing larger counts and variability of bacterial species.